Waste to wealth of apple pomace valorization by past and Current extraction processes: a review - Nicky Rahmana Putra; Dwila Nur Rizkiyah; Ahmad Hazim Abdul Aziz; Mohd Azizi Che Yunus; Ibham Veza; Irianto Harny; Andy Tirta (Molecular Diversity Preservation International (MDPI), 2022)
Every year, more than 50 million metric tons of apples are produced, and apple pomace is frequently discarded as waste in the food industry. Apple pomace, a byproduct of apple juice and cider production, is used as a sustainable raw material to make valuable products such as nutraceuticals and pectin. Apple pomace contains a substantial amount of antioxidant compounds, which have been related to several health advantages. Therefore, valuable components extracted from this byproduct may be used in the food and pharmaceutical industries. The common and new technologies to obtain valuable products from apple pomace which has come from production of apple juice or cider. Especially, emphasis of new and green technique is very important and will contribute the literature. Therefore, this review discussed apple processing, pectin as a bioactive compound, the extraction methods, current applications of apple pomace byproducts, and future studies on its potential uses in food.